Determinan Leverage Optimal Di Bursa Efek Indonesia - Purwanto Widodo; Juardi Juardi (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Research on capital structure, recently characterized by the use of dynamic capital structure. The use of dynamic capital structure basically wants to know the existence of optimal leverage as hypothesized by Trade-Off Theory and Speed off Adjustment (SOA) to optimal leverage. This research tries to overcome this problem, by using dynamic panel data by using company characteristics and macroeconomic factors. The use of General Method of Moment (GMM) to overcome the problem of econometrics due to the use of dynamic models. Samples taken from manufacturing companies listing on the Indonesia Stock Exchange 2009-2015. The inference model and the determinant behavior of capital structure can be explained by Trade-Off Theory and Pecking Order Theory. The variable characteristics of the company and macro economy are significant and are marked according to the hypothesis. The findings of this study include: the influence of profitability, size, tangibility, growth opportunity and business risk. In addition, on average companies in Indonesia can increase their debt to utilize tax shields